Bio Potential Amplifier in Noisy Environments: Challenges and Solutions - Abdel-Razzaq, Mohamed Ali Mahmoud; Behe, Haroon Abbas; Mueen, Sajjad Hayder; Ameen, Ali Abdulla Mohammed; Jawad, Yaqoub Ismail (American Journal of Botany and Bioengineering, 2025)
Operating environment has remarkable influence on bio potential amplifier. This paper analyses various noise sources showing their impact on amplifier performance. Main design considerations (input impedance, common-mode rejection ratio, bandwidth and frequency response) are considered to meet stringent requirements of clinical experiments. A detailed survey of hardware and software noise reduction techniques is provided. The importance of each technique is evaluated on the basis of severity of noise, cost and computational burden. Adaptive filter is also applied to day-to-day application to reduce motion artifact noise. Medical diagnostic systems employ bio potential amplifiers to extract physiological information from weak biopotential signals. These signals are emitted by various physiologies present in the human body and their analysis provides vital information concerning the health of the patient. The problem arises when the amplifier is situated in noisy environment. Under such circumstances, the bio potential amplifier picks up multiple noise emanating from various sources. These noise corrupt the biopotential signals and make them undecipherable. It is therefore important to analyse these noises for solution. Several techniques, both hardware and software, exist to alleviate such noise but their importance has to be reanalyzed for specific applications.